The development of argument and improvement of semantic and pragmatic aspects of oral language by investigative - Wanessa H. Pickina Silva Suzuki; Andreia de Freitas Zompero (Universidad Distrital Francisco José de Caldas, 2016)
The Language is the mechanism that allows us to share all the knowledge acquired in the learning and teaching process. Through it the scientific knowledge is arranged. The language's communicative property is the most meaningful ability which allows man to report, to reason or to refute an idea. The teaching strategies which aim to develop scientific enculturation, bring science closer to the school routine, introducing distinguished conceptions that favour problematic teaching. The investigative methodologies lead the student to develop communication abilities, specially reasoning, in scientific speech perspective. Knowing about this difficulty that the students, specifically the ones of the seventh grade of the primary school of brazil's state school, have in understanding certain parts of the contents in the subject of Science, most of the times lacking in a concrete referential idea, the theme of microorganisms was chosen to substantiate the investigative activities proposed. Therefore, the goal of this paper is to identify and to analyse the communicative abilities of language, regarding argumentation and its development, as the improvement of semantic and pragmatic aspects of language. To organize this activity of investigation, the approach of the National Research Council was used, as well as the assumption idealized by S. Toulmin, regarding the argument structure. The pragmatic and semantic abilities were referred through the theory of the Speech Acts. Analyzing the obtained data, it was possible to ascertain that some students were benefited with this methodology and were able to absorb concepts that substantiated and contributed to the structural quality of the argument. Besides that, it was realized that the improvement of the semantic and pragmatic aspects framed an efficient communication.